2012
DOI: 10.4049/jimmunol.1102460
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expansion of Allogeneic Regulatory T Cells by Hepatic Stellate Cells: Role of Endotoxin and Implications for Allograft Tolerance

Abstract: Hepatic stellate cells (HSCs) may play an important role in hepatic immune regulation by producing numerous cytokines/chemokines, and expressing Ag-presenting and T cell co-regulatory molecules. Due to disruption of the endothelial barrier during cold-ischemic storage and reperfusion of liver grafts, HSCs can interact directly with cells of the immune system. Endotoxin (LPS), levels of which increase in liver diseases and transplantation, stimulates the synthesis of many mediators by HSCs. We hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(143 citation statements)
references
References 79 publications
9
134
0
Order By: Relevance
“…An important stimulator of the synthesis of chemokines and cytokines by murine and human HSCs is LPS [50,[53][54][55][56]. Table 14.1 lists cytokines and chemokines expressed by rat HSCs and increased robustly within 1-3 h of stimulation with LPS [50].…”
Section: Hscs Produce Inflammatory and Immunoregulatory Cytokines Andmentioning
confidence: 98%
“…An important stimulator of the synthesis of chemokines and cytokines by murine and human HSCs is LPS [50,[53][54][55][56]. Table 14.1 lists cytokines and chemokines expressed by rat HSCs and increased robustly within 1-3 h of stimulation with LPS [50].…”
Section: Hscs Produce Inflammatory and Immunoregulatory Cytokines Andmentioning
confidence: 98%
“…LPS-tolerized macrophages, which are re-challenged by LPS after prior exposure to LPS, are regarded as the common model of hypo-responsiveness for SAIS (13)(14)(15). The studies showed that endotoxin tolerance reprograms TLR4 signaling with decreased proinflammatory cytokine production but increased anti-proinflammatory cytokine production by decreasing TLR4 expression, blocking tyrosine phosphorylation of TLR4 and TIRAP, TLR4-MyD88, and IRAK1-MyD88 assemblies, attenuating activation of IRAK4 and IRAK1, inhibiting K63-linked ubiquitination of IRAK1 and TRAF6, or increasing expression of negative regulators IRAK-M, SHIP-1, suppressor of cytokine signaling 1 (SOCS1), and A20 (13, 16 -18).…”
mentioning
confidence: 99%
“…Recent innovative work [42,43] has extended these observations to show that HSC can regulate allogeneic T-cell responses through the PD-L1(= B7-H1)-PD-1 pathway and that HSC can protect pancreatic islet allografts from rejection by enhancing alloreactive T-cell apoptosis. More recent data [44] suggest that HSC (that interact physically with DC in hepatic sinusoids (Fig. 4)) can regulate the function of DC and promote Treg expansion, with implications for the outcome of liver transplantation.…”
Section: The Role Of Hepatic DC In Regulation Of Alloimmunity and Tolmentioning
confidence: 97%